2011
DOI: 10.1007/s10482-011-9649-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of DNA base excision repair in filamentation in Escherichia coli K-12 adhered to epithelial HEp-2 cells

Abstract: Base excision repair (BER) is dedicated to the repair of oxidative DNA damage caused by reactive oxygen species generated by chemical and physical agents or by metabolism which can react with DNA and cause a variety of mutations. Epithelial cells are typically the first type of host cell to come into contact with potential microbial invaders. In this work, we have evaluated whether the adherence to human epithelial cells causes DNA damage and associated filamentation. Experiments concerning adherence to HEp-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…Moreover, this adherence to glass was accompanied by filamentous bacterial growth in the xthA mutant (BW9091) () and especially in the triple xthA nfo nth mutant (BW535) (). This result is similar to that observed in the adherence to HEp-2 cells where BER mutants (BW9091 and BW535) also revealed higher filamentation (Costa et al , 2012). Nevertheless, the wild-type strain (AB1157) presented rare filaments () and the strain deficient in SOS induction ( lexA Ind − , DM49) did not exhibit bacterial cell filamentation ().…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, this adherence to glass was accompanied by filamentous bacterial growth in the xthA mutant (BW9091) () and especially in the triple xthA nfo nth mutant (BW535) (). This result is similar to that observed in the adherence to HEp-2 cells where BER mutants (BW9091 and BW535) also revealed higher filamentation (Costa et al , 2012). Nevertheless, the wild-type strain (AB1157) presented rare filaments () and the strain deficient in SOS induction ( lexA Ind − , DM49) did not exhibit bacterial cell filamentation ().…”
Section: Resultssupporting
confidence: 88%
“…We showed previously that adherence to HEp-2 cells is accompanied by filamentous growth and SOS induction in a wild-type strain (AB1157), and especially in BER mutants (BW9091 and BW535) (Costa et al , 2012). Therefore, we wondered whether the attachment to glass could lead to DNA damage in the same BER mutants, resulting in a filamentation response.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…These results are in accordance with the hypothesis that low-intensity laser effects could depend on the genetic characteristics of cells [8,18], in particular those related to DNA repair systems [19,29,30,33]. In fact, it has been reported that the filamentation phenotype was increased for BW9091 and BW535 (exonuclease III, endonuclease III, endonuclease triple mutant) and inhibited by complementation of these mutants with a wild type exonuclease III gene in an assay of cell adherence [45].…”
Section: Discussionsupporting
confidence: 90%
“…3; Additional file 1: Figure S1). Elongated bacterial shape has been observed in stressed conditions such as oxidative stress, nutrient limitation, DNA damages, antibiotics exposure, or extensive recombinant protein expression [2931] altering DNA replication and cell division. The plausible reason for this might be that the E. coli might have recognized stress and exhibited elongated cell morphology only within a narrow range of stress conditions, i.e., when the growth rate during the chemostat was D = 0.1 h −1 , corresponding to early stationary phase, while the SEM observation and flow cytometry analysis were performed using mid log phase cells in batch cultures.…”
Section: Discussionmentioning
confidence: 99%